Exploring the Role of Ethics in Digital Marketing to Enhance Trust, Commitment, and Repurchase Intention in E-Commerce in Indonesia - Ma'arif, M. Syamsul; Albari, Albari (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the impact of ethical practices in digital marketing, consumer trust, and consumer commitment on repurchase intention in e-commerce platforms in Indonesia. In the rapidly evolving digital landscape, the application of ethics in digital marketing plays a crucial role in shaping consumer behavior. The research adopts a quantitative approach, involving 450 respondents selected through convenience sampling. Data was collected using an online questionnaire distributed via Google Forms. To analyze the data, this study employs Structural Equation Modeling (SEM) with the assistance of AMOS version 24.0. The results indicate that all tested hypotheses have a significant effect. Specifically, the findings suggest that ethical practices in digital marketing positively influence consumer trust, which in turn contributes to increased consumer commitment and repurchase intention. These findings provide important insights for e-commerce practitioners in Indonesia, highlighting the need to incorporate ethical elements into their digital marketing strategies, given their significant impact on enhancing trust, fostering commitment, and driving repurchase intentions among consumers. Keywords: Ethical Practices in Digital Marketing, Consumer Trust, Consumer Commitment, Repurchase Intention, E-Commerce in Indonesia.